Teknik Penanganan Deformasi Pengelasan Elemen Pendukung Konstruksi Bangunan Kapal - Bulan Purnama; Taufiqur Rachman (Zona Laut : Jurnal Inovasi Sains Dan Teknologi Kelautan, 2024)
Deformation is a change in shape due to stress in the metal caused by expansion of the weld metal during the heating and cooling process which has the potential to reduce the structural strength and operational efficiency of the ship. The forms of deformation due to the welding process on supporting elements of ship construction are shrinkage deformation, corner deformation, deformationbuckling, and longitudinal deformation. This research analyzes the factors that cause welding deformation in supporting elements of ship construction, identifies existing welding deformation handling techniques, and analyzes the effectiveness of deformation handling techniques to maintain the structural integrity of ship buildings. It is hoped that this research can make a scientific contribution in improving the quality, aesthetics and safety of ship construction, as well as increasing the efficiency of the shipbuilding production process. The research method used is in the form of a literature study by accessing library documents or secondary data from existing case studies. This deformation is caused by heat in the material, the expansion coefficient and the heat propagation coefficient. Techniques for handling welding deformation on supporting elements of ship construction can be applied by heating (firing) and cooling. This will provide excellent results if carried out with the correct procedures in handling deformations that occur between supporting elements of ship construction during the fabrication process. Keyword: Dari kata kunci abstrak